Health for all children - Alan Emond (Oxford, United Kingdom : Oxford University Press, 2019)
The new edition of Health for all Children, the leading authority in the field, has been fully revised and updated to incorporate the key updates and developments on how the health of children can best be protected and promoted, making it essential reading for anyone involved in the care and welfare of children
Keywords: Child; POLITICAL SCIENCE Public Policy Social Services & Welfare; Health Promotion; Children; Child Health Services